Anterior inferior cerebellar artery (AICA) aneurysms: a radiological study of 15 consecutive patients - Muhammad, Sajjad; Hafez, Ahmad; Kaukovalta, Hanna; Rezai Jahromi, Behnam; Kivisaari, Riku; Hänggi, Daniel; Niemelä, Mika (Frontiers in Radiology, 2023)
The aneurysms of the anterior inferior cerebellar artery (AICA) are rare lesions of the posterior circulation and to treat them is challenging. We aim to present anatomical and morphological characteristics of AICA aneurysms in a series of 15 patients.The DSA and CT angiography images of AICA aneurysms in 15 consecutive patients were analyzed retrospectively. Different anatomical characteristics were quantified, including morphology, location, width, neck width, length, bottleneck factor, and aspect ratio.Eighty percent of the patients were females. The age was 52.4 ± 9.6 (mean ± SD) years. 11 patients were smokers. Ten patients had a saccular aneurysm and five patients had a fusiform aneurysm. Aneurysm in 10 patients were located in the proximal segment, in three patients in the meatal segment, and in two patients in the distal segment. Ten out of 15 patients presented with a ruptured aneurysm. The size of AICA aneurysms was 14.8 ± 18.9 mm (mean ± SD). The aspect ratio was 0.92 ± 0.47 (mean ± SD) and bottleneck factor was 1.66 ± 1.65 (mean ± SD).AICA aneurysms are rare lesions of posterior circulation predominantly found in females, present predominantly with subarachnoid hemorrhage, and are mostly large in size.